2009
DOI: 10.1007/s11442-009-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of land use/cover change on storage and quality of soil organic carbon in midsubtropical mountainous area of southern China

Abstract: Land use/cover change (LUCC) is widely recognized as one of the most important driving forces of global carbon cycles. The influence of converting native forest into plantations, secondary forest, orchard and arable land on stores and quality of soil organic carbon (SOC) was investigated in mid-subtropical mountainous area of southern China. The results showed that LUCC had led to great decreases in SOC stocks and quality. Considerable SOC and light-fraction organic carbon (LFOC) had been stored in the native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
1
30
0
1
Order By: Relevance
“…At global and regional scales, change from forest to cropland also significantly reduced SOC content at 0e60 cm depth (Guo and Gifford, 2002;Don et al, 2011). To this end, we re-analyzed data from previous studies focused on issues other than the effect of land use change on subsoil SOC, and found that SOC stock in subsoil (20e100 cm) could be reduced by 26e61% after native forest conversion to secondary forests, plantations, and agricultural land in the tropics and subtropics (Pibumrung et al, 2008;Yang et al, 2009b). These values were similar to our results of 23e40% reduction in SOC stock in subsoil following land use change.…”
Section: Organic C Losses In Top and Subsoil Following Land Use Changementioning
confidence: 98%
See 1 more Smart Citation
“…At global and regional scales, change from forest to cropland also significantly reduced SOC content at 0e60 cm depth (Guo and Gifford, 2002;Don et al, 2011). To this end, we re-analyzed data from previous studies focused on issues other than the effect of land use change on subsoil SOC, and found that SOC stock in subsoil (20e100 cm) could be reduced by 26e61% after native forest conversion to secondary forests, plantations, and agricultural land in the tropics and subtropics (Pibumrung et al, 2008;Yang et al, 2009b). These values were similar to our results of 23e40% reduction in SOC stock in subsoil following land use change.…”
Section: Organic C Losses In Top and Subsoil Following Land Use Changementioning
confidence: 98%
“…Large areas of evergreen broadleaved forest have been slashed, burned and subsequently replaced by highly productive plantations, orchards, and sloping tillage. These rapid land use changes have led to serious environmental problems, including water-induced soil erosion, soil fertility decline, productivity loss, and decrease in ecosystem resilience (Yang et al, 2009b;Sheng et al, 2010). In addition, subtropical China is characterized by widespread mountain and hilly landforms with steep slopes, frequent heavy rainfall, and severe soil erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported large amount of SOC storage in forest compared to agricultural land (e.g. Khormali et al, 2009;Yang et al, 2009;Saha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soil also plays a vital role in controlling global climate change because it acts as the main source and sink for greenhouse gases and is the biggest C reservoir of terrestrial ecosystem (Post and Kwon, 2000;Prentice et al, 2001;Lal, 2004). Land use/cover change (LUCC) is widely recognized as one of the most important driving forces of soil C balance (Watson et al, 2000;Yang et al, 2009), and its effect on the soil C pool is also one of the links with great uncertainty in the current study on the carbon cycle (Gao et al, 2004). The results obtained by Houghton (2003) indicated that globally, the C loss amounted to about 156 PgC of the terrestrial ecosystem from 1850 to 2000 caused by the land use change, contributing about 33% of the increased atmospheric CO 2 concentration.…”
Section: Introductionmentioning
confidence: 99%